STRATEGI KOMUNIKASI PEMASARAN FRESHOES DALAM MENINGKATKAN JUMLAH KONSUMEN - Putra Nuryadin, Nikon Andalas; Andayani, Sri; Nasution, Ute Chairus (Universitas 17 Agustus 1945 Surabaya, 2017)
This research is of interest the authors of the independent small business world, which aims tofind marketing communications strategy Freshoes done in improving the consumer. The author usesdescriptive qualitative research that describes the marketing communications strategy do freshoes.The data collected to determine the marketing communication strategy using in-depth interviews andobservations of the owner Freshoes, employees as key informants and consumers as well as to test theinformant keabsahaan data. Results of the study also proves that the marketing communicationsstrategy to increase the number of consumers who do freshoes there are two things: first, the theory ofmarketing communication explains that marketers inform you as clearly as he explained the productsthat will be on offer to the target is the customer, the marketing mix (Place, Price, Place, promotion)of these four factors of marketing communication strategies to improve consumers is a factor ofPersonal Selling and promotion (promotion). Researchers recommend that marketing should bepropagated through other media such as social media Facebook and so forth and create your ownwebsite in order to facilitate the wider community.Keywords: Marketing Communications Strategy, Strategy in increasing customer